Association between dairy consumption and menopausal symptoms: A cross-sectional study among Iranian postmenopausal women. (June 2020) - Abshirini, Maryam; Siassi, Fereydoun; Koohdani, Fariba; Qorbani, Mostafa; Golpour-Hamedani, Sahar; Khosravi, Shahla; Aslani, Zahra; Soleymani, Mahshid; Sotoudeh, Gity
Abstract: The association between dairy food consumption and menopausal symptoms was evaluated with a cross-sectional study conducted on 393 postmenopausal women. A food frequency questionnaire was used to assess dietary intake over a year; menopausal symptoms were measured using a menopause rating scale (MRS) questionnaire. The total MRS score was the sum of the somatic, psychological, and urogenital scores. After adjustment for age, years since menopause, education level, BMI, physical activity, energy intake, healthy eating index and fibre intake, higher total dairy intake was related to lower somatic (β −0.184; P -value <0.001), psychological (β −0.155; P -value 0.002) and total MRS (β −0.184; P -value <0.001) scores. In addition, higher intake of low-fat dairy was associated with lower somatic (β −0.175; P -value <0.001), psychological (β −0.181; P -value <0.001) and total MRS (β −0.189; P -value <0.001) scores. Regular consumption of low fat dairy may be beneficial in improving somatic and psychological symptoms of menopause.